STUDI POTENSI DESTINASI WISATA DESA SAPORKREN KABUPATEN RAJA AMPAT - Lod Gamaliel Komiter; Parino Rahardjo (Jurusan Arsitektur dan Perencanaan, 2023)
Saporkren Village has natural and cultural potential as a tourist destination. To be more attractive to tourist visits, a more planned village potential development concept is needed and in accordance with recommendations for the progress of the Saporkren Tourism Village. The potential of a tourism village is the potential for a village-based tourist destination where there are various factors that support the progress of a tourist village. The potential includes policies, location, site, landscape/culture, accommodation/facilities, services and prices. As well as the feasibility factors of tourist villages such as Cultural and Natural Resources, Promotion and Preservation of Cultural Resources, Economic Sustainability, Social Sustainability, Environmental Sustainability, Tourism Potential and Development and Value Chain Integration, Tourism Governance and Priority, Infrastructure and Connectivity, Health, Safety and Security. The purpose of this study was to determine the natural and cultural potential, as well as the physical condition of the Saporkren Tourist Village and also to determine the condition of the buildings and infrastructure of the Saporkren Tourist Village. This potential study will produce conclusions and recommendations that can be used for the development of the Saporkren Tourism Village. Keywords: potential; Saporkren; tourism; tourist destinations; tourist village Abstrak Desa Saporkren memiliki potensi alam dan budaya sebagai destinasi wisata. Untuk lebih menarik kunjungan wisata diperlukan konsep pengembangan potensi desa yang lebih terencana dan sesuai dengan rekomendasi demi kemajuan Desa Wisata Saporkren. Potensi Desa wisata adalah potensi destinasi wisata berbasis desa dimana ada berbagai faktor yang mendukung dalam kemajuan suatu desa wisata. Adapun potensi tersebut seperti kebijakan, lokasi, tapak, lansekap/culture, akomodasi/fasilitas, pelayanan dan harga. Serta faktor-faktor kelayakan desa wisata seperti Sumber Daya Budaya dan Alam, Promosi dan Pelestarian Sumber Daya Budaya, Keberlanjutan Ekonomi, Keberlanjutan Sosial, Kelestarian Lingkungan, Potensi dan Pengembangan Pariwisata dan Integrasi Rantai Nilai, Tata Kelola dan Prioritas Pariwisata, Infrastruktur dan Konektivitas, Kesehatan, Keselamatan dan Keamanan. Tujuan penelitian ini untuk mengetahui potensi alam dan budaya, serta kondisi fisik Desa Wisata Saporkren dan juga untuk mengetahui kondisi bangunan dan infrastuktur Desa Wisata Saporkren. Studi potensi ini akan menghasilkan kesimpulan dan rekomendasi yang bisa digunakan untuk pengembangan Desa Wisata Saporkren.